Universal health coverage: The way forward - Ashok Kumar Jindal (Wolters Kluwer Medknow Publications, 2014)
Universal health coverage (UHC) is the means to provide accessible and appropriate health services to all citizens without financial hardships. India, an emerging economy with demographic window of opportunity has been facing dual burden of diseases in midst of multiple transitions. Health situation in the country despite quantum improvements in recent past has enormous challenges with urban-rural and interstate differentials. Successful national programs exists, but lack ability to provide and sustain UHC. Achieving UHC require sustained mechanisms for health financing and to provide financial protection through national health packages. There is a need to ensure universal access to medicines, vaccines and emerging technologies along with development of Human Resources for Health (HRH). Health service, management, and institutional reforms are required along with enhanced focus on social determinants of health and citizen engagement. UHC is the way for providing health assurance and enlarging scope of primary health care to nook and corners of the country.